Os bancos de sementes comunitários na construção dos territórios de Esperança: o caso do assentamento Três Irmãos/ PB - Nascimento, Juliano Moreira do (2011)
The valorization of the cultivation of sustenance is related to the construction of new territories, strengthened by various local cultures, in many cases, assigned to a mystical value, social, historical, political and economical. In Brazil, mainly in the Northeast, the tradition of seed storage today reduced due to new techniques introduced by agricultural modernization is a form of guarantee power in times of drought and of quality seeds for planting at the right time. This thesis aims to analyze a form of pleasant resistance to the process of capital‟s domination in the agriculture, the Seed Bank comunities (BSC acronyn in Portuguese), through the case study of BSC from settlement called Três Irmãos. To do this, we highlight as specific objectives: a) to debate the meanings on the territory, rural development and sustainable agricultural practices, while categories of theoretical reasoning and analysis; b) redeem the historical process of territorial from Sertão of Paraíba - one region from the state- formation in the light of uneven development of capitalism and combined in the field; c) retrieve and discuss the historical process of construction of the territory of the settlement and BSC Três Irmãos (Triunfo PB); d) understand the social, economic, cultural and political dynamics of seed banks and their reflections on the territories. The locus of research was the settlement Três Irmãos composed of 74 families, distributed in 6 parts: Três Irmãos, Mulunguzinho, Tabuleiro Grande, Cróa and Vertente, located in the microregion of Cajazeiras. Choosing this Settlement occurred due to the fact he was the first in the Sertão of Paraiba to develop a Community seed bank in the 1990s being the third in Brazil. The methodology used was a case study of quantitative and qualitative approach with emphasis on second. Data collection was performed from Exploratory Research interviews, testimonials of family farmers, people from NGOs and technicians, plus comments, field visits and attendance at events. The Paper is divided into four chapters, besides the introduction and final considerations. It is concluded that seed storage represents a form of resistance to negative impacts on the field, caused by the prevailing capitalist model; Furthermore, it contributes to the strengthening of territories of hope by sharing knowledge and seeds to farmers about their localities; also, collaborates with the rescue of new and old peasant production techniques, in Paraíba, which culminates in the State Party of Seed of Passion.